La educación emocional en la formación del profesorado de Educación Inicial. - Mullo Quishpe, Evelyn Sofía (2018)
In this research work was carried out as a study problem "Emotional Education in Teacher Training of Initial Education." It is focused in the educational field considering as objective to identify the level of Emotional Education that the teachers of initial education have through the observation for the development of the emotional competencies of the teachers. It will be based on the research processes and the qualitative and quantitative methodology will be used. The techniques used were the interview, survey and observation, with their respective instruments the interview guide, questionnaire and observation sheet, which allowed to collect information to teachers and authorities about the problems studied. The results found allowed to determine that the majority of teachers don’t know about emotional education and they haven’t received workshops from the Ministry of Education. It is tried that emotional education is a skill that helps present and future teachers, it is true that it is essential to prepare academically, teachers must have a solid education in all the sciences which their work is based: pedagogy, psychology, philosophy, etc., but there is an element that constitutes the guiding axis of a good practice: the personal development of the educator, mental health and self-fulfillment will give solid bases to carry out the work successfully.